Manure and Residue Inputs Maintained Soil Organic Carbon in Upper Midwest Conservation Production Systems. Issue 4 (8th June 2018) - Weyers, Sharon L.; Johnson, Jane M.F.; Archer, David W.; Gesch, Russ W.; Forcella, Frank
Abstract : Core Ideas: Management potential to enhance sustainability was evaluated through change in SOC. Manure application stabilized but did not increase SOC in organic systems. Loss of SOC was prevented with manure and high residue inputs. Conservation production systems are needed in the upper Midwest to slow soil and nutrient loss through tillage‐induced erosion. However, producers are reluctant to adapt no‐till strategies because of the cool‐wet climate. With focus on strip‐tillage (ST) and a diverse 4‐yr (4y) crop rotation as alternatives to no‐till, we assessed eight integrated strategies under both conventional (CNV) and organic (ORG) management. These included conventional moldboard plow + disk tillage (CT), with (YF) fertilizer or manure, with no (NF) amendments, and 2‐yr (2y) rotations: ST‐YF‐4y, ST‐NF‐4y, ST‐YF‐2y, ST‐NF‐2y, CT‐YF‐4y, CT‐NF‐4y, CT‐YF‐2y, and CT‐NF‐2y. Temporal change and loss rates of total soil organic C (SOC) and N (SON) were measured using the equivalent soil mass method for the 0‐ to 30‐ and 0‐ to 60‐cm profiles. Soil was sampled in autumn, after harvest and before tillage, in the first, second, sixth, and eighth years of rotation between 2002 and 2009. In 2002, management had no effect on baseline measurements. Average SOC and SON from 2002–2009 were significantly greater in YF strategy systems, with no other differences among strategies occurring. Net loss in SOC, but not SON, occurred over time, and estimated rates of loss were significant for all individual management strategies, but not all integrated strategies. Under CNV, estimated rates of loss were significant in all but the CNV‐CT‐NF‐2y system. In contrast, under ORG, estimated rates of loss were significant only for ORG‐CT‐NF‐4y and ORG‐ST‐NF‐4y systems. Animal manure, particularly in combination with high residue inputs, had a positive impact for maintaining SOC.